STUDI KELAYAKAN TAKSI WANITA “WOMEN TAXI”DI KOTA SURABAYA - Guntur Khoiru Wildan; Benny Lianto; I Made Ronyastra (CALYPTRA, 2020)
The number of crimes that occurred at this time to make the security of the community a little disturbed, especially women in Indonesia. Because in 2016 Komnas Perempuan recorded 16.217 cases of crimes experienced by women. One suitable business opportunity to solve the above problem is to establish a Women Taxi. A feasibility study is needed to find out whether the business is feasible or not. The results on the market aspect show that effective demand for Women Taxi in 2018 is 290.430 consumers, effective demand continues to increase until 2022. In the technical aspect, the business location and location of the base are selected by the A HP method. The selec ted business location is loca ted on J L. Raya Kendung, while the location of the selec ted base 10 places spread in the city of Surabaya. On the aspect of management is defined form of this business entity is CV with 75% capital comes fr om the owner of CV and 25% comes fr om BCA loan. On the financial aspect is known TPC value of Rp26.792.176.124,0 0. NPV value of Rp19.446.473.183,00. DPP of this business for 3 years 5 months 27 days, while IRR is greater than MARR (10.44%), which is 34.87%.